Ethical Use of Artificial Intelligence Tools by Future Teachers - González-Cervera, Ana; Burgueño-López, Jorge; Urosa-Sanz, Belén (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2026)
This study analyses how pre-service teachers use artificial intelligence (AI) tools in academic contexts and their perceptions and practices regarding ethical use. A quantitative, cross-sectional design was applied to 136 teacher education students from a Spanish university using convenience sampling. A custom questionnaire comprised three sections: general AI usage frequency, usage in specific academic tasks, and a Likert scale assessing ethical perceptions. Findings indicate that AI tools are mostly used for content comprehension, academic writing, and exam preparation, while their application in time management, presentations, and research remains limited. Ethically, students mostly engage in responsible practices, though issues such as blind reliance or uncited use still emerge. The discussion highlights a partial and functionally restricted integration of AI, constrained by insufficient digital competence and limited ethical training. No significant differences were found by age, academic major, or year of study. The study concludes that targeted training programs are urgently needed to promote ethical AI literacy among future teachers, ensuring a critical, autonomous, and pedagogically sound integration of these tools in higher education.